2019
DOI: 10.1002/jgc4.1206
|View full text |Cite
|
Sign up to set email alerts
|

How to inform at‐risk relatives? Attitudes of 1379 Dutch patients, relatives, and members of the general population

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…In this question, we purposefully chose to exclude a pre-defined response option with "a personal meeting" since in clinical practice, personal counselling would still require a first contact (by letter or phone) in which the reason for the consultation must be given. Previous studies show that "a personal meeting" is reported as the most attractive option if such a response alternative is offered [37].…”
Section: Preferred Mode Of Communicationmentioning
confidence: 99%
“…In this question, we purposefully chose to exclude a pre-defined response option with "a personal meeting" since in clinical practice, personal counselling would still require a first contact (by letter or phone) in which the reason for the consultation must be given. Previous studies show that "a personal meeting" is reported as the most attractive option if such a response alternative is offered [37].…”
Section: Preferred Mode Of Communicationmentioning
confidence: 99%
“…Privacy laws worldwide prohibit healthcare providers from revealing genetic information to anyone except the tested individual. The responsibility to share genetic test results lies almost exclusively with the mutation carrier, who has the right not to disclose this information [ 17 , 18 ]. This communication strategy has significant limitations in both ensuring contact with the appropriate people and the transmission of accurate information [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potential benefits of genetic testing are not being effectively communicated through family networks, leading to more than 50% of at-risk individuals not using genetic services and not receiving important information from a credible source [21][22][23]. Second-degree and male relatives, those living further away, and those with an estranged relationship with the mutation carrier are most likely not to be informed about genetic testing [24,25]. Despite these difficulties, a family-based approach in communicating hereditary cancer risk is advantageous because it may reach relatives through the social bonds and functions already existing within the family network, and it is not limited to those in contact with the health care system [26].…”
Section: Introductionmentioning
confidence: 99%